2019
DOI: 10.2465/jmps.180710
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of melt of soda melilite composition at high pressure

Abstract: The viscosity of melt of soda melilite (CaNaAlSi 2 O 7) composition was measured using the falling sphere method with synchrotron X-ray radiography. This composition of melt was used as a model basalt, because the ratio of the non-bridging oxygen (NBO) and the tetrahedrally coordinated (T) cation is 0.67. We observed a viscosity minimum between 2 and 4 GPa. This finding shows that the partially depolymerized melt (NBO/T = 0.67) has a viscosity minimum under high pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Experimental conditions and results ρ h and ρ 0 were adopted as the upper and lower density limits, respectively. viscosity at high pressures is the same as that at ambient pressure (Suzuki et al, 2011;Suzuki, 2019). This study showed that the viscosity of the KTS4 melt decreased with increasing pressure and reached a minimum at around 3.3 GPa.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…Experimental conditions and results ρ h and ρ 0 were adopted as the upper and lower density limits, respectively. viscosity at high pressures is the same as that at ambient pressure (Suzuki et al, 2011;Suzuki, 2019). This study showed that the viscosity of the KTS4 melt decreased with increasing pressure and reached a minimum at around 3.3 GPa.…”
Section: Resultssupporting
confidence: 53%
“…I performed in situ falling-sphere viscometry by using the MAX-III high pressure apparatus at the BL-14C2 and AR-NE7A at the Photon Factory, High Energy Accelerator Research Organization, Tsukuba, Japan. This experimental procedure has been reported elsewhere (Suzuki et al, 2011;Suzuki, 2018Suzuki, , 2019. Glass with a KTS4 composition was synthesized from a mixture of dried powders of reagent-grade oxides (SiO 2 and TiO 2 ) and carbonate (K 2 CO 3 ).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation